Management of Grant Collections in Special Libraries - Isnani, Khafifah; Samosir, Fransiska Timoria; Sa'diyah, Lailatus (Progam Studi Ilmu Perpustakaan UIN Sumatera Utara Medan, 2024)
The research provides a comprehensive overview of the process of managing grant collections and efforts to overcome challenges in the diplomatic library of the Ministry of Foreign Affairs. The expected outcome of this research is to contribute to a better understanding of grant collection management in the diplomatic library environment of the Ministry of Foreign Affairs. The study focuses on the management of grant collections in the diplomatic library, emphasizing the processes that must be undertaken before being presented to library users. The research utilizes qualitative methods through interviews, observations. Challenges faced in managing grant collections include limited storage space and a shortage of human resources, posing challenges to collection management. Efforts made by librarians to address these challenges include, first, separating collections that are not suitable, and second, addressing the shortage of human resources by collaborating with universities to supplement human resources through the acceptance of internship students. The importance of this research is to use it as a comparison material that will be applied in other libraries, so that the application of grant management in other libraries can be even better.